The Role of Records Management and Good Governance at Sheema District Local Government Headquarters. - Asasiira, Priscah (Kabale University, 2023)
The purpose of the study was to establish the role of records management in good governance at Sheema District Local Government Headquarters. It was guided by the following specific objectives namely; establishing the different types of records managed at Sheema District Local Government, assessing the role of records management and good governance at Sheema District Local Government, establishing the challenges associated with records management practices at Sheema District Local Government and suggesting possible solutions to the challenges associated with records management practices at Sheema District Local Government. The study targeted a population of 80 respondents. A descriptive research design was used and a sample of 67 respondents was used for the study. Questionnaires and interview guides were used in data collections. The findings showed that majority of respondents indicated fiscal records, administration records, legal records, contractual records, historical records, research records and electronic records. Findings further indicated that records controls the creation and growth of records, reduces operating costs, improves efficiency and productivity, helps to assimilate new records management technologies and take advantage of their many benefits, safeguards vital information, supports better decision making, preserves the corporate memory, minimizes litigation risks, fosters professionalism in running business and ensures regulatory compliance. From the findings, challenges like lack of awareness on the importance of records management, insufficient funds to support records management activities, inadequate staff and training, outdated archival legislation, appraisal backlogs, lack of sound records management programmes and reluctance to facilitate access to information were identified. The study recommended that there should be development and implementation of records management programmes, clearance of accumulated backlogs of unprocessed records, development of records management strategies, marketing the archives and records management service, placement of archival institutions, capacity building in archives and records management, updating of archival legislation and facilitating access to information.